International Students and Generative Artificial Intelligence: A Cross-Cultural Exploration of HE Academic Integrity Policy - Bannister, Peter; Alcalde Peñalver, Elena; Santamaría Urbieta, Alexandra (Journal of International Students, 2024)
An exploratory analysis of tertiary education GenAI academic integrity policies has been undertaken, to examine provision for international students, having been identified as vulnerable to bias and integrity challenges associated with these technologies. A qualitative document analysis of 131 HE institutions (HEI) policies across 11 countries reveals mostly scant consideration of international students’ needs, with the majority lacking any explicit provision. A subsequent SWOT analysis of exceptions to this generally indicates strengths in acknowledging diverse learner assumptions but weaknesses regarding specificity in articulating tailored expectations and support. These novel findings suggest international students have been largely overlooked by HEIs here despite generally significant economic contributions, reflecting the tenets of the commodification of HE. Results also highlight an urgent need to address gaps by incorporating international student voices in policy development,. Not addressing these issues risks exacerbating frictions, undermining academic integrity, and further disadvantaging this group in policy responses to GenAI.